Glufosinate enhances the activity of protoporphyrinogen oxidase inhibitors. Issue 4 (12th July 2020) - Takano, Hudson K; Beffa, Roland; Preston, Christopher; Westra, Philip; Dayan, Franck E
Abstract: Glufosinate inhibits glutamine synthetase (GS), a key enzyme for amino acid metabolism and photorespiration. Protoporphyrinogen oxidase (PPO) inhibitors block chlorophyll biosynthesis and cause protoporphyrin accumulation, a highly photodynamic intermediate. Both herbicides ultimately lead to plant death by a massive accumulation of reactive oxygen species (ROS) through different mechanisms. We investigated a potential synergistic effect by the mixture of the two herbicide mechanisms of action (MoAs). The tank mix between a low rate of glufosinate (280 g ai ha −1 ) with an ultra-low dose of saflufenacil (1 g ha −1 ) provided enhanced herbicidal activity compared with the products applied individually on Palmer amaranth ( Amaranthus palmeri S. Watson). The synergism between the two herbicides was also confirmed by isobole analysis and field trials. The herbicide combination provided high levels of efficacy when applied at low temperature and low humidity. Mechanistically, glufosinate caused a transient accumulation of glutamate, the building block for chlorophyll biosynthesis. Consequently, inhibition of both GS and PPO resulted in greater accumulation of protoporphyrin and ROS, forming the physiological basis for the synergism between glufosinate and PPO inhibitors. While the synergy between the two herbicide MoAs provided excellent efficacy on weeds, it caused low injury to PPO-resistant waterhemp [ Amaranthus tuberculatus (Moq.) Sauer] and high injury to both glufosinate-resistant and glufosinate-susceptible soybean [ Glycine max (L.) Merr.]. Glufosinate enhances the activity of PPO inhibitors through glutamate and protoporphyrin accumulation, leading to increased levels of ROS and lipid peroxidation. The synergism between the two herbicide MoAs can help to overcome environmental effects limiting the efficacy of glufosinate. Future research is needed to optimize the uses for this herbicidal composition across different cropping systems.